Comparison of anthropometric measurements associated with the risk of endoscopic erosive esophagitis: A cross-sectional study. Issue 6 (November 2017) - Park, Jae Keun; Lim, Yaeji; Lee, Hyuk; Kim, Tae Jun; Choi, Yoon-Ho; Min, Yang Won; Min, Byung-Hoon; Lee, Jun Haeng; Rhee, Poong-Lyul; Kim, Jae J.
Summary: Background: In this cross-sectional study, we assessed five anthropometric measurements to determine the most reliable indicator of the erosive esophagitis (EE) risk: body mass index (BMI), waist circumference (WC), waist to height ratio (WHtR), a body shape index (ABSI), and body roundness index (BRI). Methods: This study included 182, 407 participants who underwent an esophagogastroduodenoscopy as part of a routine health check-up. We used the area under the receiver-operating characteristic curve (AUC) to assess the discriminatory power of each anthropometric measure as an indicator of EE risk. Results: The prevalence of EE increased per quartile for all five anthropometric measurements in patients of both sexes (1 st quartile vs. 4th quartile, all P <  0.05). ABSI had the lowest AUCs for EE in both sexes (AUC: 0.524, 95% CI: 0.519–0.529 for male patients; AUC: 0.524, 95% CI: 0.513–0.535 for female patients). In contrast, BRI was the best predictor of EE in male patients (OR: 2.095, 95% CI: 1.982–2.215, P <  0.0001), and WC was the best predictor of EE in female patients (OR: 2.028, 95% CI: 1.785–2.307, P  < 0.0001). WC showed the highest AUC values for EE in both male patients (AUC: 0.571, 95% CI: 0.566–0.576) and female patients (AUC: 0.596, 95% CI: 0.585–0.608). Conclusions: BRI and WC were the most relevant indicators of EE risk in male and female patients, respectively. ABSI was the least reliable indicator of EE risk in patients of both sexes.